Macrophage, a potential targeted therapeutic immune cell for cardiomyopathy - Chen, Ganyi; Jiang, Hongwei; Yao, Yiwei; Tao, Zhonghao; Chen, Wen; Huang, Fuhua; Chen, Xin (Frontiers in Cell and Developmental Biology, 2022)
Cardiomyopathy is an important cause of heart failure, causing systolic and diastolic dysfunction and promoting adverse cardiac remodeling. Macrophages, as important immune cells of the heart, play a decisive role in inflammation and fibrosis. What’s more, there are functional and phenotypic differences between exogenous macrophages and cardiac resident macrophages during cardiac injury. Although experimental evidence shows promise for macrophage-targeted therapy in cardiomyopathy, clinical translation remains challenging. In this article, the molecular mechanism of macrophages in cardiomyopathy is discussed in detail in combination with the literature, and the issues and considerations of clinical treatment strategies for myocardial fibrosis are analyzed.